Exploring the Immunotherapeutic Potential of Oleocanthal against Murine Cutaneous Leishmaniasis - Karampetsou, Kalliopi; Koutsoni, Olga S.; Badounas, Fotis; Angelis, Apostolis; Gogou, Georgia; Skaltsounis, Leandros-Alexios; Halabalaki, Maria; Dotsika, Eleni (Planta Medica, 2022)
Leishmaniasis is a major tropical disease with increasing global incidence. Due to limited therapeutic options with severe drawbacks, the discovery of alternative treatments based on natural bioactive compounds is important. In our previous studies we have pointed out the antileishmanial activities of olive tree-derived molecules. In this study, we aimed to investigate the in vitro and in vivo antileishmanial as well as the in vivo immunomodulatory effects of oleocanthal, a molecule that has recently gained increasing scientific attention. Pure oleocanthal was isolated from extra virgin olive oil through extraction and chromatography techniques. The in vitro antileishmanial effects of oleocanthal were examined with a resazurin-based assay, while its in vivo efficacy was evaluated in Leishmaniamajor-infected BALB/c mice by determining footpad induration, parasite load in popliteal lymph nodes, histopathological outcome, antibody production, cytokine profile of stimulated splenocytes and immune gene expression, at three weeks after the termination of treatment. Oleocanthal demonstrated in vitro antileishmanial effect against both L. major promastigotes and intracellular amastigotes. This effect was further documented in vivo as demonstrated by the suppressed footpad thickness, the decreased parasite load and the inflammatory cell influx at the infection site. Oleocanthal treatment led to the dominance of a Th1-type immunity linked with resistance against the disease. This study establishes strong scientific evidence for olive tree-derived natural products as possible antileishmanial agents and provides an adding value to the scientific research of oleocanthal.
Keywords: Olea europaea L. (Oleaceae); cutaneous leishmaniasis; oleocanthal; in vitro and in vivo antileishmanial effect; immunomodulation